Induction of EBV latent membrane protein-2A (LMP2A)-specific T cells and construction of individualized TCR-engineered T cells for EBV-associated malignancies. Issue 7 (1st July 2021) - Zhang, Chaoting; Tan, Qin; Li, Shance; Shen, Luyan; Zhang, Jingtao; Liu, Ying; Yang, Wenjun; Lu, Zheming
Abstract : Background: Latent membrane protein-2A (LMP2A)-specific TCR-engineered T cells could be a promising treatment approach to Epstein–Barr virus-associated malignancies. However, previous studies mainly reported LMP2A-reactive TCRs only focusing on specific HLA subtypes and corresponding epitopes, and thus, they were only suitable for patients with specific HLA. Methods: Due to hugely varied HLA subtypes and presented LMP2A epitopes in different individuals, our study attempted to develop an individualized approach, based on the weekly in vitro stimulation of peripheral T cells for 2 weeks with autologous dendritic cells (DCs) pulsed with a pool of LMP2A peptides covering LMP2A whole protein and combination analysis of high throughput TCRβ sequencing of prestimulated and poststimulated T cells and single-cell TCR sequencing of poststimulated T cells, and to identify LMP2A-specific TCRs of which poststimulated frequencies significantly increased than corresponding prestimulated frequencies. Results: Following this approach, multiple LMP2A-reactive TCRs were identified, optimized and cloned into lentiviral vector, and then transduced into peripheral T cells. These engineerd T cells were demonstrated to specifically recognize the LMP2A presented by autologous DCs and lymphoblastoid cell lines in vitro and in vivo. Conclusions: This approach provides an efficient procedure to isolate individualized LMP2A-specific TCRs for basic and translational research, as well as for clinical applications.